Functional evaluation pre and post physical exercise program for patients in hemodialysis - De Lima, Fabiano F.; De Miranda, Regina C. V. [UNESP]; Rossi E Silva, Renata C. [UNESP]; Monteiro, Henrique L. [UNESP]; Yen, Lin S.; Fahur, Barbara S.; Padulla, Susimary Aparecida Trevizan [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2013)
Model Study: An experimental study Introduction: Chronic Kidney Disease (CKD) refers to a syndromic diagnosis which leads to a progressive and irreversible loss of renal function. A hemodialysis patient may have limitations in functional capacity, pulmonary function and respiratory musclular strength impacting in quality of life. Objective: To evaluate the effects of an exercise program on pulmonary function, functional capacity, quality of life and pain in patients undergoing hemodialysis. Methodology: The study included 28 patients of both genders, women and men aged between 40 and 60 years undergoing dialysis at the Kidney Institute, Santa Casa de Misericordia in Presidente Prudente-SP. Primary outcomes included respiratory muscular strength measurements assessed by manovacuometry. The functional capacity was evaluated by a six minute walking test. A life quality questionnaire was applied to evaluate quality of life (SF36-KDQOL). Lung function was evaluated by spirometry. Pain was assessed by a visual analogue scale. The exercise program consisted of training 3 times a week for 40 minutes on hemodialysis during eight weeks. At the end of the program all patients were reassessed. Results: There was no significant difference in the values of FVC and FEV1 before and after the exercise program as well as the index Tiffenau. The value of post MIP was significantly higher than the value obtained in the pre program. For variable MEP no significant difference was found. Functional capacity evaluations showed that there were no significant differences (p> 0.05). The evaluation of quality of life, about the domains of specific areas of CKD showed statistical significance when comparing the list of symptoms and problems with overloading of renal disease and professional role. Indicators related to pain were significantly reduced after the program (P <0.05). Discussion: A chronic kidney patient faces complex situations of physical, social and financial aspects. Although no statistically significant results were found in all variables, the study corroborates to others found in the literature, which suggests that an exercise program can be positive for this population. Conclusion: Although lung capacity and functional capacity did not submit changes to the end of the study, reduced levels of pain, fatigue and dyspnea suggest improvement in functional performance after exercise programs.
Avaliação funcional pré e pós-programa de exercício físico de pacientes em hemodiálise
Keywords: Hemodialysis; Physical activity; Quality of life; Spirometry